2017
DOI: 10.3389/fphys.2017.01011
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Evaluation of Chronic Nanosilver Toxicity to Adult Zebrafish

Abstract: Nanotechnology is rapidly growing with nanoparticles produced and utilized in a wide range of commercial products worldwide. Among the different types of nanomaterials produced, silver nanoparticles (AgNPs) occupy a predominant position and they are used in electronics, clothing, food industry, cosmetics and medical devices. Nanosilver has also showed excellent performance in antibacterial application. Nowadays, the increasing use of AgNPs has put the evidence on their possible toxicity to the human health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 24 publications
0
47
0
1
Order By: Relevance
“…Several studies have showed a correlation between the concentration of toxic substances and the capacity of different organisms to respond to exposure. The biological response can encompass change of vitality, morphological and physiological modifications or genetic damage (Morgano et al, ; Perugini et al, ; Salvaggio et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have showed a correlation between the concentration of toxic substances and the capacity of different organisms to respond to exposure. The biological response can encompass change of vitality, morphological and physiological modifications or genetic damage (Morgano et al, ; Perugini et al, ; Salvaggio et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore they present an organ primarily involved in the accumulation of xenobiotics (Costa, Bouchon, Van Straalen, Sousa, & Ribeiro, ; Hussein, Obuid‐Allah, Mohammad, Scott‐Fordsmand, & Abd El‐Wakeil, ; Longo et al, ; Mazzei et al, ), the hepatopancreas and a detoxification system of heavy metals which involves the induction of the expression of the metallothioneins (Droutsa et al, ; Mazzei et al, ). Metallothioneins 1 (MT1) are called exposure biomarkers and are part of a superfamily of low molecular mass cytoplasmic proteins, characterized by a high cysteine content and the absence of aromatic aminoacids and histidine, that are involved in the regulation of essential metals metabolism, in heavy metal detoxification and in protection against oxidative stress (Ferrante et al, ; Salvaggio et al, ; Viarengo, Burlando, Ceratto, & Panfoli, ) and also in metallic nanoparticles detoxification (Brundo et al, ; Pecoraro, Marino, et al, ; Pecoraro, Salvaggio, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several organisms are used as models in toxicological studies (Conte et al, 2016;Copat et al, 2012;D'Agata et al, 2014;De Domenico et al, 2011;Kanold, Wang, Brümmer, & Šiller, 2016;Mazzei et al, 2014;Scuderi et al, 2014;Wang, Jia, Zhu, Zhang, & Wang, 2017;Xiao, Vijver, Chen, & Peijnenburg, 2015), and among these, presently, zebrafish is considered the model organism, best suited, for toxicological testing Buccheri et al, 2016;Pecoraro et al, 2018;Pecoraro, D'Angelo, et al, 2017;Pecoraro, Salvaggio, et al, 2017;Salvaggio et al, 2016;Wang et al, 2011). Different types of parameters are used to evaluate NPs toxicity such as hatching F I G U R E 3 Scanning electron microscopy of the corneal surface reveals the presence of microvilli and microplicae and fingerprintlike structures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on animal models have shown that NPs can be potentially toxic (Hu et al, ; Lankveld et al, ), and that toxicity of NPs depends certainly on their size (Lankveld et al, ). Among the different animal models, zebrafish or Danio rerio is considered an excellent model for nanotoxicity studies for some particular features of these animals (Brundo et al, ; Lee, Nallathamby, Browning, Osgood, & Xu, ; Pecoraro et al, ; Pecoraro et al, ; Pecoraro et al, ; Salvaggio et al, ; Sarasamma et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers, used in previous studies, have proved excellent biomarkers of exposure to metallic xenobiotic in different animals (Droutsa et al, ; Ferrante et al, ; Mazzei et al, ; Piscopo et al, ; Salvaggio et al, ); they have been chosen because it has been shown that they intervene in the detoxification processes of metallic nanoparticles (Brundo et al, ; Pecoraro, Marino, et al, ; Pecoraro, Salvaggio, et al, ).…”
Section: Introductionmentioning
confidence: 99%